Economic benefits to colombia with the signing of peace agreement (2016)
The armed conflict has lived Colombia has been one of the longest in world history, has tried to solve for decades by governments that have, however past, although they have had approaches these have not been very fruitful. Today has risen negotiating table is very close to signing a peace agreement between the government and the FARC. In this regard there have been consequences of economic decline, therefore herein is intended to carry out a review of the economic benefits that would have Colombia with the signing of the agreement, based on historical arguments for this, a literary review was conducted as a source primary to develop and analyze the issue.